Exploiting the transient response of a single degree-of-freedom oscillator for the purpose of energy harvesting - Gatti, Gianluca; Brennan, Michael J. [UNESP] (My University, 2015)
Vibration-based energy harvesters have been intensively studied recently because of the need to power wireless devices or to augment the use of batteries. When time-unlimited harmonic excitation is provided to a single degree of freedom oscillator, good performance is achieved if the device is tuned to the excitation frequency. In such a situation, the harvested energy is inversely proportional to the suspension damping, which is thus sought to be very low. However, for time-limited excitation very low damping involves relatively long transi-ents, both at the beginning and at the end of the response, which can affect the harvesting performance considerably. This paper presents an investigation on the design of a linear spring-mass-damper system to scavenge energy from time-limited oscillations, which could be a more likely situation in some practical applications, compared to a state-state assump-Tion.